2019
DOI: 10.1039/c9ra03846a
|View full text |Cite
|
Sign up to set email alerts
|

La2O3-coated Li2ZnTi3O8@C as a high performance anode for lithium-ion batteries

Abstract: LZTO@C@La2O3 coated with composite protective layers with excellent electrochemical performance has been synthesized using a simple solid-state method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 35 publications
0
5
1
Order By: Relevance
“…However, it can be seen that Nb-doping greatly improves the cycling performance of LZTO at high temperature, indicating that its structure is tremendously stabilized via Nb-doping. Its cycling performance at a high temperature of 55 °C surpasses many previous reports. , In addition, Nb-doping obviously enhances the rate capability of LZTO at a low temperature of 0 °C (Figure b). Especially for LZTN1O, at the current density of 0.8 A g –1 , 178.8 mA h g –1 is still kept at the 60th cycle.…”
Section: Resultscontrasting
confidence: 49%
See 1 more Smart Citation
“…However, it can be seen that Nb-doping greatly improves the cycling performance of LZTO at high temperature, indicating that its structure is tremendously stabilized via Nb-doping. Its cycling performance at a high temperature of 55 °C surpasses many previous reports. , In addition, Nb-doping obviously enhances the rate capability of LZTO at a low temperature of 0 °C (Figure b). Especially for LZTN1O, at the current density of 0.8 A g –1 , 178.8 mA h g –1 is still kept at the 60th cycle.…”
Section: Resultscontrasting
confidence: 49%
“…Its cycling performance at a high temperature of 55 °C surpasses many previous reports. 45,59 In addition, Nb-doping obviously enhances the rate capability of LZTO at a low temperature of 0 °C (Figure 6b). Especially for LZTN1O, at the current density of 0.8 A g −1 , 178.8 mA h g −1 is still kept at the 60th cycle.…”
Section: ■ Results and Discussionmentioning
confidence: 97%
“…No diffraction peaks are observed from carbon in the XRD pattern due to its amorphous nature, but it also caused an increase in cell parameter. , The unit cell parameter a (Å) of LZTO-1 and LZTO-2 is 8.37105 and 8.3117, respectively. Carbon coating can also be beneficial in the sense that it may prevent the direct interaction of the electrolyte with the electrode, thus preventing the side reactions which are responsible for the weakening of the interface …”
Section: Resultsmentioning
confidence: 99%
“…Carbon coating can also be beneficial in the sense that it may prevent the direct interaction of the electrolyte with the electrode, thus preventing the side reactions which are responsible for the weakening of the interface. 20 Raman spectroscopy was utilized to confirm the carbon deposition in the Li 2 ZnTi 3−x Nb x O 8 /C (x = 0.05) material. Two prominent bands approximately at 1340 and 1589 cm −1 might be credited to the D band and G band, respectively, Figure 3.…”
Section: Methodsmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9] Therefore, the innovation of preparation technology related to the membrane of LIBs is also in urgent need of a breakthrough. [10][11][12][12][13][14][15][16] Changqing Zhu et al acquired an aramid nanober/polyphenylene sulde (ANFs/PPS) nonwoven composite separator via a paper-making method. 17 It was found that the introduction of polar ANFs is helpful for lithium-ion transfer between the electrodes, and the cycling retention rate of the battery with the composite separator consequently reached 92% at 0.5C, much higher than that of the cell with a PP membrane (73%).…”
Section: Introductionmentioning
confidence: 99%